SEPARATION OF POWERS IN THE STATES OF CENTRAL ASIA AND THE CAUCASUS - ZHURAKULOV, Furkat (CENTRAL ASIA AND THE CAUCASUS, 2011)
Today practical realization of the classical principle of the separation of powers in all states (in the states of Central Asia and the Caucasus, two regions of key importance, in particular) has acquired special urgency as directly related to global, national, and regional security. Indeed, coordinated functioning of independent and interacting branches of state power (legislative, executive, and judicial) is part of a reasonable and adequate foreign policy which stems from the country’s national interests and to a great extent helps the state deal with threats, risks, and challenges.The experience of state development and the application of the separation of powers principle in nine countries (Afghanistan, Armenia, Azerbaijan, Georgia, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan) has already confronted the expert community with a set of far from simple questions about the role of the traditional forms of governance; the way the classical principles should be borrowed and applied; and the impact of starting conditions on what the governments, parliaments, and courts of the newly independent states can do. Not infrequently those undertaking the reforms refer to the threats to national security to explain what has or has not been done; in some countries reforms degenerated into a pure formality, etc.I have deliberately included Afghanistan, the specific conditions of which set it apart from the post-Soviet states, and will show how it is developing into a unique platform on which historical and national elements are being strengthened to move the country toward democracy. All the developed democracies are closely following the political reforms underway in Afghanistan and are extending it ever larger amounts of humanitarian aid.It is expected that the discussion about the future political system of Afghanistan that will unfold at the May 2012 meeting in Chicago with NATO allies and partners convened “to shape the next phase of this transition” will be very intensive.